CaMK modulates sensory neural activity to control longevity and proteostasis - Ranran Zhao; Weiqi Ge; Weikang Xue; Zaidong Deng; Jiaze Liu; Kaiqi Wang; Youngnam N. Jin; Yanxun V. Yu (Proceedings of the National Academy of Sciences, 2025)
The impact of neural activity on aging and longevity remains poorly understood, with limited understanding of the specific neuron groups and molecular mechanisms that regulate lifespan. In this study, we uncover a correlation between human longevity and reduced CaMK4 expression in the frontal cortex. We further show that this link is conserved in Caenorhabditis elegans , where the loss of the homolog CMK-1 leads to increased longevity and enhanced proteostasis. These beneficial effects are primarily driven by suppressed excitation in the primary thermosensory AFD neurons, particularly at elevated temperatures that trigger hyperactivation. In the thermosensory neural circuit, suppression of AFD neuron activity promotes the release of INS-1/insulin from AIZ, which in turn activates DAF-16/FOXO in the intestine. Our findings reveal a causal mechanism through which sensory neural activity governs lifespan and organismal proteostasis, highlighting the significance of CaMK in shaping these processes through the regulation of neural activity.